Ethiopian population dermatoglyphic study reveals linguistic stratification of diversity. - Seile Yohannes; Endashaw Bekele (PLoS ONE, 2015)
The manifestation of ethnic, blood type, & gender-wise population variations regarding Dermatoglyphic manifestations are of interest to assess intra-group diversity and differentiation. The present study reports on the analysis of qualitaive and quantitative finger Dermatoglyphic traits of 382 individuals cross-sectionally sampled from an administrative region of Ethiopia, consisting of five ethnic cohorts from the Afro-Asiatic & Nilo-Saharan affiliations. These Dermatoglyphic parameters were then applied in the assessment of diversity & differentiation, including Heterozygosity, Fixation, Panmixia, Wahlund's variance, Nei's measure of genetic diversity, and thumb & finger pattern genotypes, which were inturn used in homology inferences as summarized by a Neighbour-Joining tree constructed from Nei's standard genetic distance. Results revealed significant correlation between Dermatoglyphics & population parameters that were further found to be in concordance with the historical accounts of the ethnic groups. Such inductions as the ancient north-eastern presence and subsequent admixure events of the Oromos (PII= 15.01), the high diversity of the Amharas (H= 0.1978, F= 0.6453, and P= 0.4144), and the Nilo-Saharan origin of the Berta group (PII= 10.66) are evidences to this. The study has further tested the possibility of applying Dermatoglyphics in population genetic & anthropologic research, highlighting on the prospect of developing a method to trace back population origins & ancient movement patterns. Additionally, linguistic clustering was deemed significant for the Ethiopian population, coinciding with recent genome wide studies that have ascertained that linguistic clustering as to being more crucial than the geographical patterning in the Ethiopian context. Finally, Dermatoglyphic markers have been proven to be endowed with a strong potential as non-invasive preliminary tools applicable prior to genetic studies to analyze ethnically sub-divided populations and also to reveal the stratification mechanism in play.